FRI0546 GENDER DIFFERENCES OF RHEUMATIC DISEASES IN MEXICAN POPULATION: DATA FROM THE MEXICAN BIOLOGICS REGISTRY. (2nd June 2020) - Rivera Teran, V.; Alpizar-Rodriguez, D.; Sicsik, S.; Irazoque-Palazuelos, F.; Miranda, D.; Vega-Morales, D.; Casasola, J. C.; Carrilo, S.; Castillo, A.; Duran Barragan, S.; Muñoz, O.; Paz, A.; et al.
Abstract : Background: Most autoimmune diseases are more prevalent in women. Symptom severity, disease progression, response to therapy and overall survival differ between males and females with rheumatic diseases. Objectives: To identify the characteristics of autoimmune diseases presentation and treatment between male and female population using information from the Mexican Adverse Events Registry (BIOBADAMEX). Methods: BIOBADAMEX is a Mexican ongoing cohort that collects the information of patients using biologic and biosimilar drugs since 2016. For this study we included all patients enrolled in the registry and compared baseline clinical and disease characteristics, treatment and presence of adverse events between genders. We used logistic regression to analyze univariable associations. Results: A total of 655 participants were analysed, of which 82% were female (Table 1 ). We found women were older with a median of 53 years compared to 46 years in men (OR 1.02, CI 1.0-1.1). Smoking was higher in men (16%) compared to women (5%), (OR 0.3, CI 0.2-0.6). Women had longer disease duration, 9 years compared to 7 years in men (OR 1, CI 1.0-1.1). Rheumatoid arthritis (RA) was more prevalent in women (OR 2.7, CI 1-6.9), while ankylosing spondylitis (AS) and psoriatic arthritis (PsA) were more prevalent in men (OR 0.2, CI 0.1-0.4, and OR 0.3, CI 0.1-0.9 respectively). Women had more comorbidities than men (OR 1.8, CI 1.1-2.8) and used steroids more frequently (OR 1.7, CI 1.1-2.7). Differences in disease activity were not found, however we noticed high activity scores among participants. Conclusion: In our study we found sex differences regarding age and disease duration, being higher in women. As expected, the prevalence of RA was higher in women and AS and PsA in men. Overall, women used more steroids than men. An interesting finding was that patients had high disease activity. Future longitudinal analyses will allow us to analyse sex differences in disease progression and treatment response. References: [1] Ortona E et al. Ann Ist Super Sanita 2016;52(2):205-12 [2] Ngo ST et al. Front Neuroendocrinol 2014;3(3):347-69 Disclosure of Interests: Vijaya Rivera Teran: None declared, Deshire Alpizar-Rodriguez: None declared, Sandra Sicsik: None declared, Fedra Irazoque-Palazuelos Consultant of: Bristol-Myers Squibb, Janssen, Pfizer Inc, Roche and UCB, Dafhne Miranda: None declared, David Vega-Morales: None declared, Julio Cesar Casasola: None declared, Sandra Carrilo: None declared, angel castillo: None declared, Sergio Duran Barragan: None declared, Omar Muñoz: None declared, Aleni Paz: None declared, Angélica Peña: None declared, Alfonso Torres: None declared, Daniel Xavier Xibille Friedmann Consultant of: Lilly, Abbvie, Speakers bureau: Lilly, Abbvie, Azucena Ramos: None declared, José Francisco Moctezuma: None declared, Francisco Aceves: None declared, Estefania Torres: None declared, Natalia Santana: None declared, Miguel Vazquez: None declared, Erick Zamora: None declared, Francisco Guerrero: None declared, Claudia Zepeda: None declared, Melanea Rivera: None declared, Kitzia Alvarado: None declared, Cesar Francisco Pacheco Tena: None declared